LAT1 Protein Content Increases Following 12 Weeks of Resistance Exercise Training in Human Skeletal Muscle - Roberson, Paul A.; Mobley, C. Brooks; Romero, Matthew A.; Haun, Cody T.; Osburn, Shelby C.; Mumford, Petey W.; Vann, Christopher G.; Greer, Rory A.; Ferrando, Arny A.; Roberts, Michael D. (Frontiers in Nutrition, 2021)
Introduction: Amino acid transporters are essential for cellular amino acid transport and promoting protein synthesis. While previous literature has demonstrated the association of amino acid transporters and protein synthesis following acute resistance exercise and amino acid supplementation, the chronic effect of resistance exercise and supplementation on amino acid transporters is unknown. The purpose herein was to determine if amino acid transporters and amino acid metabolic enzymes were related to skeletal muscle hypertrophy following resistance exercise training with different nutritional supplementation strategies. Methods: 43 college-aged males were separated into a maltodextrin placebo (PLA, n = 12), leucine (LEU, n = 14), or whey protein concentrate (WPC, n = 17) group and underwent 12 weeks of total-body resistance exercise training. Each group's supplement was standardized for total energy and fat, and LEU and WPC supplements were standardized for total leucine (6 g/d). Skeletal muscle biopsies were obtained prior to training and 72 h following each subject's last training session. Results: All groups increased type I and II fiber cross-sectional area (fCSA) following training (p < 0.050). LAT1 protein increased following training (p < 0.001) and increased more in PLA than LEU and WPC (p < 0.050). BCKDHα protein increased and ATF4 protein decreased following training (p < 0.001). Immunohistochemistry indicated total LAT1/fiber, but not membrane LAT1/fiber, increased with training (p = 0.003). Utilizing all groups, the change in ATF4 protein, but no other marker, trended to correlate with the change in fCSA (r = 0.314; p = 0.055); however, when regression analysis was used to delineate groups, the change in ATF4 protein best predicted the change in fCSA only in LEU (r2 = 0.322; p = 0.043). In C2C12 myoblasts, LAT1 protein overexpression caused a paradoxical decrease in protein synthesis levels (p = 0.002) and decrease in BCKDHα protein (p = 0.001). Conclusions: Amino acid transporters and metabolic enzymes are affected by resistance exercise training, but do not appear to dictate muscle fiber hypertrophy. In fact, overexpression of LAT1 in vitro decreased protein synthesis.